2021
DOI: 10.1177/11786469211052964
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Intermediates of L-Trp Along the Reaction Pathway of Human Indoleamine 2,3-Dioxygenase 1 and Identification of an Exo Site

Abstract: Protein dynamics governs most of the fundamental processes in the human body. Particularly, the dynamics of loops located near an active site can be involved in the positioning of the substrate and the reaction mechanism. The understanding of the functioning of dynamic loops is therefore a challenge, and often requires the use of a multi-disciplinary approach mixing, for example, crystallographic experiments and molecular dynamics simulations. In the present work, the dynamic behavior of the JK-loop of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Analysis of the ferrous IDO spin state can be approached in a similar way, beginning with visual comparison of the IDO and ferrous sulfate Kβ 1,3 peak positions. This qualitative analysis would appear to suggest substantial HS character in crystals of the ferrous enzyme, in agreement with earlier room temperature resonance Raman, MCD, and UV–vis absorbance studies that reported spectral features consistent with a five-coordinate HS heme cofactor. ,, X-ray crystallographic models depicting the ferrous enzyme further support this proposal, as the loop containing Ala264 does not directly interact with the metal ion, and no alternative distal ligand was observed (Figure D). ,, However, the intensity and shape of the ferrous IDO Kβ′ peak are more consistent with an IS or LS complex. We hypothesize that LS character may be introduced, at least in part, due to the cryogenic conditions (100 K) under which these data were collected, as has been inexplicably observed for other water/histidine-coordinated heme complexes. , Such behavior can likewise be employed to rationalize overlap with the ferric IDO spectrum, suggesting an upper bound of 25% LS contamination.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Analysis of the ferrous IDO spin state can be approached in a similar way, beginning with visual comparison of the IDO and ferrous sulfate Kβ 1,3 peak positions. This qualitative analysis would appear to suggest substantial HS character in crystals of the ferrous enzyme, in agreement with earlier room temperature resonance Raman, MCD, and UV–vis absorbance studies that reported spectral features consistent with a five-coordinate HS heme cofactor. ,, X-ray crystallographic models depicting the ferrous enzyme further support this proposal, as the loop containing Ala264 does not directly interact with the metal ion, and no alternative distal ligand was observed (Figure D). ,, However, the intensity and shape of the ferrous IDO Kβ′ peak are more consistent with an IS or LS complex. We hypothesize that LS character may be introduced, at least in part, due to the cryogenic conditions (100 K) under which these data were collected, as has been inexplicably observed for other water/histidine-coordinated heme complexes. , Such behavior can likewise be employed to rationalize overlap with the ferric IDO spectrum, suggesting an upper bound of 25% LS contamination.…”
supporting
confidence: 87%
“…41,44,46 X-ray crystallographic models depicting the ferrous enzyme further support this proposal, as the loop containing Ala264 does not directly interact with the metal ion, and no alternative distal ligand was observed (Figure 4D). 40,47,48 However, the intensity and shape of the ferrous IDO Kβ′ peak are more consistent with an IS or LS complex. We hypothesize that LS character may be introduced, at least in part, due to the cryogenic conditions (100 K) under which these data were collected, as has been inexplicably observed for other water/histidine-coordinated heme complexes.…”
mentioning
confidence: 97%
“…Different observations can explain such discrepancies. The inconsistent activity profile of compound 18 may be explained by the presence of an additional binding pocket ( exo site) in the small domain of IDO1, which is able to bind indole bearing compounds [ 46 , 47 ]. Hence, the binding potency of the indole derivative 18 (K d = 4.83 ± 0.61) against recombinant IDO1 may likely be associated with the interaction with the exo site, located outside of the catalytic cleft, affecting less the catalytic activity of IDO1.…”
Section: Resultsmentioning
confidence: 99%
“…4D). 43,47,48 However, the intensity and shape of the ferrous IDO K peak is more consistent with an IS or LS complex. We hypothesize that LS character may be introduced, at least in part, due to the cryogenic conditions (100 K) under which these data were collected, as has been inexplicably observed for other water/histidine-coordinated heme complexes.…”
Section: The Spectrometer Was Commissioned At the Advanced Photon Sou...mentioning
confidence: 99%